Direitos humanos nos serviços de saúde mental: representações sociais de profissionais - Menezes, Lívia Sales Cirilo de (2015)
The citizenship and the fulfillment of human rights have become guiding principles of the new forms of mental health care, grounded in the psychiatric reform, yet still seem to be actions that hurt the respect for human rights. In the daily life of the new mental health services, the goal is that human rights are respected. Historically laws were created to address this issue, such as the Law 10.216. The laws and ordinances are configured as a legal apparatus in ensuring these rights, but it is possible to notice a discrepancy between knowing the rights of the mentally ill and consolidate strategies that seek this guarantee. This study aimed to identify the social representations of human rights of professionals of mental health services - CAPS. The objectives of this study were answered through a research which theoretical and methodological bases were developed by Moscovici and Willem Doise. This study deals with an ex post facto research of the quantitative and qualitative type. We interviewed 60 graduated professionals in the mental health services and used as instruments: a socio-demographic questionnaire, scales of psychosocial measures and a semi-structured interview. This study follows rules established by the National Health Committee according to Resolution 196, with regard to the ethical procedures, being submitted and approved by the Ethics Committee in Research of the State University of Paraiba. In the data analysis we used the Bardin content analysis, statistical analysis and the statistical program ALCESTE. The results indicated that the social representations of human rights were anchored in the psychiatric reform and implementation of CAPS services. Most participants reported that there are changes, even if subtle, in the way mental illness is viewed by society. The dendrogram was composed by two groups: Reform Evaluation and re socialization and citizenship. The first one grouped the categories: criticism to assistance and legislation and the second group gathered the categories: cause of diseases, role of professionals and social inclusion. While the professionals reported knowing important aspects of psychiatric reform and the new attendance policy, the daily services of the human rights effective actions appear to be scarce. The professionals also reported limitations related to a large number of activities, little disclosure about the rights and other issues. As regards the level of involvement in human rights, the results showed that at the personal level, the professionals evaluated that should be involved and have been involved in the rights issue, while at the governmental level, respondents rated that the Government should engage in advocacy of rights, but in practice little is done. These results indicate the need for reflection and evaluation of services so that there is an intersection between theory and practice and concomitantly an effective search for the fulfillment of human rights of people with mental disorders.